STUDENTS’ PREFERENCE OF DIGITAL OR PRINTED BOOKS/READING MATERIALS - Kharisma, Alfiah; Wulyani, Anik Nunuk; Astuti, Utari Praba (Universitas Negeri Malang, 2021)
This survey study aims to obtain information associated with the 7th graders' preference for reading digital/online and printed books. The data was obtained from an online questionnaire which was distributed to the 7th graders of one state junior high school in Lumajang Regency. The findings of this study shows that the majority of the students prefer to read printed books/reading materials rather than the digital books. This indicates that it is important for both teachers and students to understand what types of books are appropriate to improve students’ knowledge in the learning process.